“That’s what I believe while in the group”: Third age groups and the emerging of hidden faces of sexuality (Research, Society and Development, 2021)
Objective: to describe the influence of elderly groups on the sexuality of the elderly. Methodology: This is a descriptive, exploratory study, with a qualitative approach, carried out with 15 elderly people participating in a group of senior citizens. The data were collected in October 2014, using the creative-sensitive method, with the realization of the almanac dynamics and submitted to the analysis of the Pecheutian discourse. Results: The elderly group shows itself as a space that exerts a relevant influence on the sexuality of the elderly, manifesting itself as a locus that favors the creation and maintenance of bonds of love, which enables the awakening and understanding of sexuality in a multidimensional way and that provides support to overcome prejudices and taboos. Conclusion: It is up to health professionals to glimpse faces, perhaps hidden, and direct their actions, taking care of these spaces through health promotion and prevention activities, with a view to planning specific actions and aiming at comprehensive care for the elderly.